2021
DOI: 10.1088/1674-1137/ac1ef9
|View full text |Cite
|
Sign up to set email alerts
|

Production of light-flavor and single-charmed hadrons in pp collisions at TeV in an equal-velocity quark combination model *

Abstract: We apply an equal-velocity quark combination model to study the production of light-flavor hadrons and single-charmed hadrons at midrapidity in the collisions at TeV. We find that the experimental data for the spectra of and exhibit the quark number scaling property, which clearly indicates the quark combination mechanism at hadronization. Experimental data for the spectra of , , , , , and are systematically described by the model. The non-monotonic dependence of the ratio is naturally explained, and we find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…We see that there is a stronger suppression in more central collisions in the p T range 4 GeV < p T < 10 GeV. Figure 4b shows f Here, T AA is the average nuclear overlap function [31], dσ pp c /dy is the p T integrated cross-section of charm quarks in pp collisions which is about 1.0 mb at √ s = 5.02 TeV [77]. The values of dN c /dy at different centralities are listed in Table 2.…”
Section: Transverse Momentum Spectra Of Charm Mesons and Baryonsmentioning
confidence: 99%
See 1 more Smart Citation
“…We see that there is a stronger suppression in more central collisions in the p T range 4 GeV < p T < 10 GeV. Figure 4b shows f Here, T AA is the average nuclear overlap function [31], dσ pp c /dy is the p T integrated cross-section of charm quarks in pp collisions which is about 1.0 mb at √ s = 5.02 TeV [77]. The values of dN c /dy at different centralities are listed in Table 2.…”
Section: Transverse Momentum Spectra Of Charm Mesons and Baryonsmentioning
confidence: 99%
“…The results for differential cross-sections of charm hadrons in pp collisions at √ s = 5.02 TeV are taken from reference [77] by some of us. Figure 9 shows R AA for prompt D 0 , D + and D * + mesons as well as Λ + c at 0-10% and 30-50% centralities.…”
Section: Nuclear Modification Factor R Aamentioning
confidence: 99%
“…[37] to explain the constituent quark number scaling (QNS) property that we found in the experimental data of p T spectra of identified hadrons in pPb collisions at LHC energy. The model is now applied to pp, pA and AA collisions at both RHIC and LHC energies, and has successfully explained the experimental data for yields, p T spectra and elliptic flow of light-flavor hadrons and those of single-charm hadrons at RHIC and LHC [38][39][40][41][42][43][44][45].…”
Section: Pt Of Hadrons In Evc Modelmentioning
confidence: 99%
“…Eqs. ( 7) and ( 8) lead to some interesting correlations among the production of different hadrons such as QNS mentioned above, which were tested by experimental data [39, [41][42][43][44][45]. Our previous works [37,40,41,43,45] have shown that Eqs.…”
Section: Pt Of Hadrons In Evc Modelmentioning
confidence: 99%